Repercusiones en los alumnos de primer curso de la implantación del Espacio Europeo - Castaño Perea, Enrique; Benito Capa, Águeda; Portela Lozano, Adelaida; Rodríguez Jiménez, Rosa María (Revista Complutense de Educación, 2007)
The Universidad Europea de Madrid pretends to converge into the European Higher Education Area being the pioneer oft he Spanish University framework. As such, has chosen to carry out the Pilot and Converge Plans that are transforming its educational means, involving all its educational community. Those Plans cover the first course students belonging to the different University school and faculties. The study intends to observe and analyze the process success and its weakness, concluding the positive implications they have reached so long in the academy results, as in its fitness to the different items involved in the starting out of the processes, and the valuation of the obtained knowledge.